The Relationship between Family Harmony with Stress, Anxiety, and Depression in Adolescents - Heni Dwi Windarwati; Amin Aji Budiman; Renny Nova; Niken Asih Laras Ati; Mira wahyu Kusumawati (Jurnal Ners, 2020)
Introduction: Adolescents are a group vulnerable to mental health problems, including stress, anxiety, and depression. This study aimed to examine the interlink of a harmonious family with stress, anxiety, and depression in adolescents.Methods: This study employed descriptive correlational design with cross-sectional approach and examined 851 high school adolescents aged between 16-18 years who were recruited using a total sampling method from five high school in Malang City. Stress, anxiety and depression in adolescents was assessed employing the Depression Anxiety Stress Scale (DASS - 21), while, to assess family harmony, a questionnaire   developed by the researcher was used. Data were analyzed through descriptive statistics and bivariate tests using Spearman Rank Correlation.Results: It was revealed that 428 adolescents (50.3%) were male, 321 adolescents (37.7%) came from parents who worked privately, and 482 adolescents (56.6%) had their parents' social status above the minimum wage standard. Eight hundred and two adolescents (94.2%) had harmonious families, while the remaining 49 adolescents (5.8%) had non-harmonious families. Our study concluded that family harmony had a significant relationship with adolescent stress levels (p-value 0.013). On the other hand, the analysis showed that family harmony was not related to adolescents' anxiety (p-value 0.071) and depression level (p-value 0.13). A harmonious family makes children mentally healthy, able to adapt to the environment while a family that is not harmonious can trigger stress because conditions are not as expected, coupled with the burden of schoolwork, stressors from teachers and peers.Conclusion:The results of the research showed that harmony in the family had a significant effect on stress in adolescents. Therefore, it is necessary to provide education and counseling to the family to prevent fights in the family so that it can reduce the emergence of stress in adolescents.